God and the secular legal system - Domingo, Rafael (Law and Christianity, 2016)
This timely book offers a theistic approach to secular legal systems and demonstrates that these systems are neither agnostic nor atheist. Critical but succinct in its approach, this book focuses on an extensive range of liberal legal approaches to religious and moral issues and subjects them to critical scrutiny from a secular perspective. Expertly written by a leading scholar, the author offers a rare combination of profundity of ideas and simplicity of expression. It is a ringing defense of the theistic conception of secular legal systems and an uncompromising attack on the agnostic and atheist conception